Modelling optical spectra and obtaining information on parameters and features of semiconductor structures - Vasiljev, V.A. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2002)
Problems of semiconductor optical spectrum identification are considered in the paper. Some models for description of optical reflection spectra in semiconductors and semiconductor structures are presented. Shown is the possibility to obtain information upon various parameters and characteristics of semiconductors and their structures by fitting theoretical spectra to experimental data. The estimation of validity and accuracy of obtained information is given.